Assessing Undergraduate Nursing Students' Integration of Theory and Practice within a Capstone Clinical Stream : Final Report. - English, Leone; Jolly, Brian; Koutoukidis, Gabrielle; Jenkins, Sommer (Office for Learning and Teaching, 2014)
Assessment of professional practice within undergraduate nursing programs entails designing user-friendly tools that assess reliably against a broad set of national competency standards and across a range of clinical contexts. Clinicians and supervisors often struggle to relate to the plethora of different tools employed by multiple nursing education providers. In 2009 Holmesglen commenced a project to develop a clinical assessment framework and tools for implementation within the Bachelor of Nursing. An assessment framework was developed and comprises of: a Professional Portfolio, Objective Structured Clinical Assessments (OSCEs), Multi-Source Assessments and Mini Health Assessments (based on the Mini-CEX used extensively in post and under-graduate medical education). The aim of this project is to further develop and evaluate the validity and reliability of the tools across the three year course, which were piloted in first semester, to ensure they are adaptable to multiple clinical contexts and facilitate integrated learning and assessment in both undergraduate nursing and other health professional courses. This document is the final report from the project.